If f ( x ) = 1 − 1 − x 2 , find f ′ ( 0 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ( x ) = ln ( f ( x ) ) = f ( x ) f ′ ( x ) = f ′ ( x ) = f ′ ( 0 ) = 1 − 1 − x 2 ⇒ f ( 0 ) = 0 2 1 ln ( 1 − ( 1 − x 2 ) 2 1 ) − 2 1 [ 1 − ( 1 − x 2 ) 2 1 1 ] ⋅ ( 1 − x 2 ) 2 1 x − 2 1 [ 1 − ( 1 − x 2 ) 2 1 ( 1 − ( 1 − x 2 ) 2 1 ) 2 1 ] ( 1 − x 2 ) 2 1 x − 2 1 x → 0 lim [ 1 − ( 1 − x 2 ) 2 1 ( 1 − ( 1 − x 2 ) 2 1 ) 2 1 ] ⋅ x → 0 lim ( 1 − x 2 ) 2 1 x The right side limit exists and evaluates to 0, therefore we are left with a 0/0 limit. x → 0 lim [ 1 − ( 1 − x 2 ) 2 1 ( 1 − ( 1 − x 2 ) 2 1 ) 2 1 ] = x → 0 lim 1 − ( 1 − x 2 ) 2 1 1 This limit obviously does not exist, so the derivative must not exist.
Problem Loading...
Note Loading...
Set Loading...
Firstly when we see a question of Differentiation we jump into Differentiating it. Ok then carry on like that.... Then you would find a 0/0 form in the answer... So then comes the tricky part... Then use limits to solve further and and get the answer. Or else you can use some substitute for x....